Effectiveness of Health Education Program on Health Care Providers’ Knowledge toward Immunization of Children at Primary Health Care Centers in Kirkuk City - Abdul Salam, Huda; Aziz, Afifa (Iraqi National Journal of Nursing Specialties, 2020)
Objectives: The study aims to evaluate effectiveness of health education program on health care providers’ knowledge toward immunization of children at primary health care centers in Kirkuk city. Methodology: A quasi –experimental study design two- group (pre-test, post-test 1 and post-test 2) conducted at primary health care centers in Kirkuk city during the period from 28 October 2019 to 10 August 2020. By collecting (50) samples divided into two groups, each one (25) participant as control & study group. The study group exposed to the education program only. Results: Results showed a clear positive effect of the program on health care providers’ knowledge towards child immunization. It indicated high significant differences for the study group between the pre-test and the post-test in the main aspects that have to do with the knowledge of health care providers’ about child immunization. Recommendations: An educational lectures should conducted & regularly updated for care providers’ about child immunization for those working in the field of vaccine and other departments within primary care centers. It also recommended more research studies should conducted on a larger sample & more primary care centers in the rest of Iraqi governorates.